2021
DOI: 10.1002/ece3.7557
|View full text |Cite
|
Sign up to set email alerts
|

Does stress mess with rodents’ heads? Influence of habitat amount and genetic factors in mandible fluctuating asymmetry in South American water rats (Nectomys squamipes, Sigmodontinae) from Brazilian Atlantic rainforest remnants

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
(123 reference statements)
1
3
0
Order By: Relevance
“…These results support earlier findings that sex has little influence on FA in the Cayo Santiago macaque population (Hallgrímsson, 1999), which aligns with many studies on FA across animal clades (Caccavo et al, 2021; Castilheiro et al, 2022; Hallgrímsson, 1993; Hopton et al, 2009; Landi et al, 2021; Van Dongen, 2015; Wauters et al, 1996) but does not align with a handful of studies in humans (Schlager & Rüdell, 2015), gorillas (Romero et al, 2022), olive baboons (Romero et al, unpublished data), lizards (Simbula et al, 2021), and shrews (Badyaev et al, 2000). These studies used a variety of data collection methods (e.g., caliper measurements, 2D photographs, 3D landmark patches) and measured different body components (e.g., mandibles, crania, femoral pores), making consistency impossible and comparisons relatively difficult.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results support earlier findings that sex has little influence on FA in the Cayo Santiago macaque population (Hallgrímsson, 1999), which aligns with many studies on FA across animal clades (Caccavo et al, 2021; Castilheiro et al, 2022; Hallgrímsson, 1993; Hopton et al, 2009; Landi et al, 2021; Van Dongen, 2015; Wauters et al, 1996) but does not align with a handful of studies in humans (Schlager & Rüdell, 2015), gorillas (Romero et al, 2022), olive baboons (Romero et al, unpublished data), lizards (Simbula et al, 2021), and shrews (Badyaev et al, 2000). These studies used a variety of data collection methods (e.g., caliper measurements, 2D photographs, 3D landmark patches) and measured different body components (e.g., mandibles, crania, femoral pores), making consistency impossible and comparisons relatively difficult.…”
Section: Discussionsupporting
confidence: 92%
“…Beyond primates, sex was not observed to drive differences in FA within either hurricane‐affected or control‐group deer mice (Hopton et al, 2009), nor in red squirrels occupying either disturbed or undisturbed woodland habitats (Wauters et al, 1996). Sex is similarly reported as a non‐significant factor upon FA within South American water rats (Caccavo et al, 2021), long‐tailed spiny rats, hairy‐tailed akodonts, wooly mouse opossums, or Amazonian red‐sided opossums (Castilheiro et al, 2022). Finally, among Italian wall lizards, sex‐based differences in FA are observed in femoral pore distribution, but not in head shape (Simbula et al, 2021), and sex‐based differences in FA are found in the mandible of common shrews exposed to habitat disturbance (Badyaev et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Instability during critical phases of foetal and postnatal development caused by environmental (e.g., parasite load, resources quality and quantity, diseases) or genetic (e.g., homozygosity, inbreeding, mutation) stressors may result in fluctuating asymmetry (Caccavo, Lemos, Maroja, & Gonçalves, 2021 ; Parsons, 1992 , but see also Lens, Dongen, Kark, & Matthysen, 2002 ). Fluctuating asymmetry refers to minor random deviations from perfect symmetry (Valen, 1962 ) and can be expressed as individual variability in the asymmetry of craniofacial features (Caccavo et al, 2021 ; Fig. 1 b) and other bilaterally symmetrical structures (Kucheravy, Waterman, & Roth, 2022 ).…”
Section: Proximate Mechanisms Underlying Facial-personality Linkmentioning
confidence: 99%
“…The skull is a key structure that holds most sensory and some food processing organs, whose intraspecific variation frequently mirrors the influence of the clinal or steep environmental gradients (see Pergams & Ashley, 2001 ; Pergams & Lawler, 2009 ; Samuels, 2009 ; Grieco & Rizk, 2010 ). Rodent cranial variation has been broadly employed as a proxy to study the ecogeographical association and potential drivers of phenotypic variability in landscapes with natural ( e.g ., Bacigalupe, Iriarte-Díaz & Bozinovic, 2002 ; Monteiro, Duarte & dos Reis, 2003 ; Cordero & Epps, 2012 ; Alvarado-Serrano, Luna & Knowles, 2013 ; Camargo et al, 2019 ) or human modified ( e.g ., Martínez et al, 2014 ; Yalkovskaya et al, 2016 ; Caccavo et al, 2021 ; also see references in Coda et al, 2021 ) environmental configurations.…”
Section: Introductionmentioning
confidence: 99%